Creative Economic Development in Increasing Sustainable Tourism Potential in Pampang Cultural Village Samarinda - Abdul Ghofur; Hendri Kurniawan; Apri Kuntariningsih; Ahmad Muthohar (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
This study examines the role of the creative economy in enhancing sustainable tourism potential in Pampang Cultural Village, Samarinda, Indonesia, and identifies strategic priorities for its development. Pampang Cultural Village is recognized for its rich cultural heritage preserved by the Dayak Kenyah community, which serves as a valuable tourism asset. Despite this potential, the contribution of creative economy activities to tourism development has not been fully optimized. Therefore, a comprehensive analysis is needed to formulate effective development strategies. This research employs a mixed qualitative–quantitative approach using the SWOT-AHP method. SWOT analysis is utilized to identify internal strengths and weaknesses as well as external opportunities and threats affecting creative economy development. Subsequently, the Analytic Hierarchy Process (AHP) is applied to determine the priority level of each strategic factor and alternative strategy. The findings indicate that the village possesses significant creative economy potential in cultural performances, handicrafts, culinary products, traditional fashion, and cultural souvenirs. Cultural authenticity emerges as the primary strength, while limited innovation capacity and digital marketing skills remain the major weaknesses. The results further reveal that the highest-priority strategy is the development of innovative creative tourism products rooted in Dayak Kenyah cultural heritage while preserving cultural authenticity. This strategy should be supported by digital promotion, human resource capacity building, stakeholder collaboration, and improvements in tourism infrastructure to achieve sustainable tourism development.